Biodiesel production from used cooking oil using green solid catalyst derived from calcined fusion waste chicken and fish bones - Tan Y, Y.H; Abdullah, M.O.; Kansedo, J.; Mubarak, N.M.; Chan, Y.S.; Nolasco-Hipolito, C. (Elsevier Ltd, 2019)
This paper evaluates the feasibility of using fusion waste chicken and fish bones as the reusable and low cost solid catalyst for synthesis of biodiesel from used cooking oil via two-step transesterification. A catalyst characterization of the prepared fusion waste chicken and fish bones catalyst was made in order to study their catalytic performance through various techniques such as Scanning Electron Microscopy (SEM), Brunauer–Emmett–Teller (BET), Particle Size Analysis (PSA), Thermal Gravimetric Analysis (TGA), Fourier Transform Infrared spectra (FTIR), Carbon Dioxide-Temperature Programmed Desorption (TPD-CO2) and X-Ray Diffraction (XRD). The used cooking oil transesterification was optimized using a response surface methodology (RSM) based on five level three variables central composite design (CCD). The RSM results revealed that the optimal operational condition for the transesterification has defined as: catalyst loading, 1.98%w/v, reaction temperature, 65 °C and time, 1.54 h, whereas the alcohol/oil molar ratio, 10:1 is a fixed variable in this study. The actual biodiesel yield of 89.5% was achieved under the predicted optimal conditions and fulfilled the ASTM D6751 biodiesel fuel standards. The promising features of the chicken and fish bones catalyst are inexpensive, easily obtained, simple work-up, simple recovery, reusability without significant drop in catalytic activity for up to four consecutive runs.